TREATMENT OF UROLITHIASIS WITH LIVER FUNCTION DISORDERS IN A NINE YEARS OLD POMERANIAN DOG - Handojo, Chindi Meilina; Soma, I Gede; Jayanti, Putu Devi; Purnama, Komang Andika (Buletin Veteriner Udayana, 2023)
The purpose of writing this report is to discuss the incidence of urolithiasis accompanied by impaired liver function in male Pomeranian dogs in carrying out diagnostic and appropriate handling and therapy of case dogs. A nine years old male Pomeranian dog weighing 2.8 kg was brought to Estimo Petshop & Clinic with complaints of hematuria , stranguria accompanied by decreased appetite and drinking for the last five days and anuria for the last two days. On physical examination, the dog was dehydrated accompanied by pale eye and mouth mucosa, bladder distension and liver can be palpated. On radiographic examination found the presence of uroliths in the bladder and urethra accompanied by an enlarged liver size. The results of the hematological examination showed that the dog had decreased hematocrit and MCV values, increased MCHC, RDW and white blood cells. The results of blood biochemical examination showed increased levels of BUN, globulins, ALT and ALKP. Urine chemistry examination showed a pH of 6.0 and abnormal in bilirubin and erythrocytes. Microscopic examination of the urine revealed the presence of calcium oxalate crystals. Based on the anamnesis, physical examination and supporting examination, the case dog was diagnosed with urolithiasis accompanied by impaired liver function. The treatment carried out was the installation of a catheter and the administration of herbal medicines containing Kejibeling and the antibiotic Ciprofloxacin HCl. However, after five days, the case dogs were brought back with a deteriorating condition. The next treatment given is cystotomy and drugs in the form of; betaine hepatoprotector injection, Ciprofloxacin HCl, cystaid dog, liver health and special diet for urinary tract disease in dogs. One week postoperatively, the case dog was able to urinate well without finding any blood. Based on the anamnesis, physical examination and supporting examinations in the form of hematological examination, blood biochemistry, radiography and urine, the case dog was diagnosed with urolithiasis accompanied by impaired liver function, where the treatment in the form of inserting a catheter and administering kejibeling extract had not been able to have a significant impact on the case dog. then an operation was performed. Therefore, to avoid urolithiasis recurrence in case dogs, it is necessary to educate the owner regarding dietary management in the form of avoiding feeds that are high in protein and calcium and further handling of impaired liver function.